Changes of clinical and echocardiographic parameters within a year after COVID-19 pneumonia in patients without cardiovascular diseases, depending on the obesity presence - E. I. Yaroslavskaya; N. E. Shirokov; D. V. Krinochkin; V. D. Garanina; I. O. Korovina; N. A. Osokina; A. V. Migacheva; A. D. Sapozhnikova; T. I. Petelina (Кардиоваскулярная терапия и профилактика)
Aim. To study the changes of clinical and echocardiographic parameters in people without cardiovascular diseases (CVDs) within a year after coronavirus disease 2019 (COVID-19) depending on the obesity presence.Material and methods. During the year after COVID-19 pneumonia, the clinical and echocardiographic parameters of 21 patients with obesity and without CVD were compared. The group both without CVDs and obesity consisted of 52 patients comparable by sex and age.Results. Newly developed CVDs were registered in 55% and 17% of the group with and without obesity, respectively. Left ventricular (LV) global longitudinal strain 3 months (-18,4±2,3 vs -20,6±2,2%, p=0,010) and one year after COVID-19 pneumonia (-18,8±1,8 vs -20,8±2,5%, p=0,021) was lower in the group with obesity. Lateral (e' later) (10,8±3,3 vs 13,1±2,9 cm/s (p=0,007)) and septal (e' sept) (8,5±2,7 vs 10,1±2,0 cm/s (p=0,011)) early diastolic mitral annulus velocity, as well as the ratio of early and late diastolic LV filling (E/A) (1,1±0,3 vs 1,2±0,3 (p=0,019)) at the end of the follow-up were lower in the group with obesity.Conclusion. In people without CVDs during a year after COVID-19 pneumonia, a high prevalence of newly developed CVD was noted in 55% and in 17% of people with and without obesity, which was accompanied by worse LV systolic and diastolic function in the group with obesity.